Experimentation of Mathematics Learning Assisted by the Digital Linktree Platform on Islamic Integrated Geometry Material to Improve Student Learning Outcomes - Zain, Nurmalia Khoirunisa; Masamah, Ulfa (Proceeding International Conference on Religion, Science and Education, 2024)
This research aims to determine the difference in students’ mathematics learning outcomes with mathematics learning assisted by the Linktree digital platform, Islamic integrated geometry material and mathematics learning without using the assistance of a digital platform. The research method used is a quantitative comparative study approach for class VIII students at Sabilurrosyad Islamic Middle School, Malang, academic year 2023/2024. Data collection techniques use observation, tests and documentation which are then analyzed using inferential analysis with the independent t-test formula. The results of the research show that there are differences in the mathematics learning outcomes of class VIII students when learning mathematics using digital platforms and not using digital platforms. Based on tests distributed by researchers, students when learning mathematics assisted by digital platforms had an average score of 16.33 so they were classified as very good. Meanwhile, students who studied mathematics without using digital platforms had an average score of 15.22, so they were classified as good. Data analysis scores show that students when using digital platforms have higher learning outcomes compared to those without using digital platforms as evidenced by test results with a t-count value of 2,351 > t-table 2,010 at a significance level of 5%. So it can be concluded that student learning outcomes in mathematics learning assisted by the Linktree digital platform in Islamic integrated geometry material are higher than those without the assistance of the digital platform.